Five writing development strategies to help academics flourish as writers - Castle, J.; Keane, M. (South African Journal of Higher Education, 2016)
Increasing the quality and quantity of published research has become an imperative for many universities in South Africa, but academic staff need more than policy mandates to flourish as writers. In this article the authors aim to inspire academic staff developers and research managers to initiate and support strategies to help academics write more and better, and to take pleasure in writing. Drawing on published literature and our own experiences, we turn a critical eye on writing development strategies used in our own research-intensive institution in Johannesburg, and strategies used in other institutions, mainly, but not only, in South Africa. We weigh up the benefits and drawbacks of five writing strategies: writing courses and workshops; writing groups; writing mentoring and coaching; PhD bootcamps; and writing retreats. We also provide a summary table of the claims made for particular strategies to promote capacity building and productivity, on the one hand, and emotional and social aspects of writing on the other hand. We conclude that by thinking critically and creatively, research managers and academic staff developers can indeed help academics to flourish as writers.